1966
DOI: 10.1002/cpt196672196
|View full text |Cite
|
Sign up to set email alerts
|

On the clinical evaluation of diuretics with particular reference to a new phthalimidine diuretic, clorexolone

Abstract: A standardized technique suitable for clinical evaluation of diuretic drugs in hospitalized patients with fiuid retention is described. The sensitivity and reliability of the method have been explored. Urinary excretion of sodium, potassum, and fiuid, as well as acute weight loss have been employed as response parameters. The assay has been applied to yield data on the absolute and comparative efficacies of a newly introduced phthalimidine diuretic, clorexolone, in a group of fifty patients. Clorexolone was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1969
1969
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The early techniques of evaluating diuretics as described by Gold, Kwit, Messeloff, Kramer, Golfins, Greiner, Goessel, Hughes & Warshaw (1960) gave the test drug and a standard drug daily or every other day and assessed weight loss. This technique has been modified by Lant, Baba & Wilson (1966) to assess biochemical variables as well as weight. However only one day was allowed between treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The early techniques of evaluating diuretics as described by Gold, Kwit, Messeloff, Kramer, Golfins, Greiner, Goessel, Hughes & Warshaw (1960) gave the test drug and a standard drug daily or every other day and assessed weight loss. This technique has been modified by Lant, Baba & Wilson (1966) to assess biochemical variables as well as weight. However only one day was allowed between treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological homeostatic mechanisms are known to be stimulated in response to diuresis (Lant, Baba & Wilson, 1966). These mechanisms comprise increased tubular reabsorption of sodium ions in the proximal tubule of the nephron (Brenner & Berliner, 1969;De Wardener, 1969) and increased aldosterone secretion (Nicholls, Espiner, Donald & Hughes, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Steady state levels of spironolactone metabolites in plasma are achieved only after several days administration (Sadee, Schroder, Leitner & Dagcioglu, 1974), and in the clinical situation there is a similar delay in observing the peak pharmacological effect of spironolactone. The latter observation led to the suggestion that single dose bioassay methods are inappropriate for testing aldosterone antagonists (Lant et aL., 1966).…”
Section: 8rmentioning
confidence: 99%
“…These workers used repeated doses of aldosterone antagonists over a three to five day period, and it has been suggested that the methods of bioassay using single doses of drug which are * approved name prorenoate potassium. commonly utilized in diuretic evaluation is inappropriate for the study of aldosterone antagonists (Lant, Baba & Wilson, 1966 (1) SC-23992, 50 mg (5 x 10 mg tablets) plps placebo spironolactone. (2) spironolactone, 125 mg (5 x 25 mg Aldactone A tablets) plus placebo SC-23992.…”
Section: Introductionmentioning
confidence: 99%